Produktivitas dan nilai nutrient beberapa jenis rumput di bawah naungan pohon karet - Syahrio Tantalo; Liman Liman; Fitria Tsani Farda; Agung Kusuma Wijaya; Yohanes Abrian Frastianto; Ignatius Anjas Pangestu (Politeknik Negeri Jember, 2021)
This study aimed to determine the productivity and nutrient content of three grasstypes with or without rubber trees shading. It was conducted in May-September 2020at Sangga Buana Village, Seputih Banyak, Central Lampung and Animal Nutrition andFood Laboratory, University of Lampung. This study used nested design with two factorsof rubber trees shaded and grass types with six replications. Both factors were shadedconditions: N0 (land without shade) and N1 (land under rubber trees shade); and grasstypes: elephant grass (A1); setaria (A2); and odot (A3). The results showed the shadeddecreased (P<0.05) leave length of each grass compared to non-shading conditions.Grass under the shade decreased their production and odot grass showed the lowestproduction (P<0.05). The number of tillers and plant height under the shade decreasedsignificantly (P<0.05) on elephant grass and setaria grass. Leaf width under the shadedecreased significantly (P<0.05) on setaria and odot grass. The shaded effected (P<0.05)nutrient content on elephant grass, setaria, and odot. It was concluded that Setariagrass (Setaria sphacelata) had the best productivity under the shaded based on yield.The nutrient content of each grass varied depending on the ability of the grass to adaptto shaded conditions.